2016
DOI: 10.1287/stsc.2015.0004
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence and Performance: A Natural Experiment in Firm Scope

Abstract: T his paper shows how interdependencies influence performance following a reduction in firm scope. We test the predictions of the theory using detailed microdata on every Peruvian fishing firm before and after a regulatory ban on mackerel fishing, finding that a reduction in the scope of activities causes the productivity of firms' legacy anchovy operations to fall sharply, before recovering in the long run. The results are most pronounced for firms with the strongest interdependencies between activities. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…We present here a possible explanation for them as an avenue for future research: That routines for managing coordination in a diversified center may also be useful for managing coordination of complexity in patient care. Prior work has shown that the routines that develop for maximizing the output of multiple units, tasks, and so on, will necessarily be different than those designed to maximize performance for only a single task (Natividad and Rawley, ; Rawley, ). These new routines that develop to maximize the use of resources across multiple tasks will likely lead to performance declines in the original task, since employees are able to perform these routines more effectively when they have fewer routines to learn (Edmondson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We present here a possible explanation for them as an avenue for future research: That routines for managing coordination in a diversified center may also be useful for managing coordination of complexity in patient care. Prior work has shown that the routines that develop for maximizing the output of multiple units, tasks, and so on, will necessarily be different than those designed to maximize performance for only a single task (Natividad and Rawley, ; Rawley, ). These new routines that develop to maximize the use of resources across multiple tasks will likely lead to performance declines in the original task, since employees are able to perform these routines more effectively when they have fewer routines to learn (Edmondson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the process of updating the routines and capabilities that create such interdependencies is likely to be difficult, time consuming, and costly to the remaining divisions within the firm over a longer time horizon. As evidence in support of this point, Natividad and Rawley () show, in the context of the Peruvian fishing industry, that firms continued to deploy their ships in a manner consistent with multi‐activity firms for several months following a regulatory ban that exogenously reduced the scope of their related activities. Similarly, Feldman () finds that legacy divestitures are negatively associated with the divesting firms' operating performance for up to 4 years after refocusing events due to the disruption of historical interdependences that developed between legacy businesses and their sister divisions.…”
Section: Theory and Hypothesesmentioning
confidence: 97%
“…Applying the insights of the literature on related diversification to refocusing suggests that removing a business that is more closely related to its sister divisions will be more costly than removing a business that is less closely related. Clearly, refocusing reduces a firm's ability to share common resources, such as knowledge, capabilities, and operating processes across businesses (Feldman, ; Natividad & Rawley, ). However, when a firm refocuses by removing a business that is less related, the extent of synergy destruction should be less pronounced, since capabilities, routines, and knowledge are shared less intensively.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…These costs stem from the inherent difficulty of adjusting and transferring resources across product categories (Hashai, ). Adjusting routines is difficult due to a cognitive tendency to transfer unchanged routines and practices between domains even though adaptation is required (Kor & Leblebici, ; Zahavi & Lavie, ); to organizational rigidity (Rawley, ); and to complementarities that are difficult to modify (Natividad & Rawley, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…While the logic of expanding product variety by leveraging key resources has been gradually confirmed and agreed upon (Neffke & Henning, ; Wan et al., ), there has been increasing interest in uncovering the causes and nature of the different costs of diversification. The extant literature has identified several sources of diversification costs, which we broadly classify as “agency costs”—the costs of increased misalignment in decision making as the firm's scope expands—(Gartenberg, ; Pierce, ; Shaver & Mezias, ), “coordination costs”—the costs of coordinating interdependent business/product units—(Zhou, ; Zhou & Wan, ), and “adjustment costs”—the various costs of adjusting and transferring practices and routines into the new product category (Hashai, ; Kor & Leblebici, ; Natividad & Rawley, ; Rawley, ; Zahavi & Lavie, ).…”
Section: Introductionmentioning
confidence: 99%